Rd as a control parameter to explore affective correlates of the tense-lax continuum - Yanushevskaya, Irena; Gobl, Christer; Ni Chasaide, Ailbhe; Murphy, Andrew (My University, 2017)
This study uses the Rd glottal waveshape parameter to simulate the phonatory tense-lax continuum and to explore its affective correlates in terms of activation and valence. Based on a natural utterance which was inverse filtered and source-parameterised, a range of synthesized stimuli varying along the tense-lax continuum were generated using Rd as a control parameter. Two additional stimuli were included, which were versions of the most lax stimuli with additional creak (lax-creaky voice). In a listening test, participants chose an emotion from a set of affective labels and indicated its perceived strength. They also indicated the naturalness of the stimulus and their confidence in their judgment. Results showed that stimuli at the tense end of the range were most frequently associated with angry, at the lax end of the range the association was with sad, and in the intermediate range, the association was with content. Results also indicate, as was found in our earlier work, that a particular stimulus can be associated with more than one affect. Overall these results show that Rd can be used as a single control parameter to generate variation along the tense-lax continuum of phonation.
INTERSPEECH 2017
PUBLISHED
Stockholm, Sweden
Keywords: Voice source; Affect; Speech synthesis; Digital Humanities